Diversified Machine Learning Techniques for Soil Management in Agriculture - Priti Prakash Jorvekar, Jayashree Rajesh Prasad (International Journal of Advanced Science and Technology, 2020)
The area of modern agriculture field acquires machine learning techniques. Though role of the machine learning techniques, tools, platforms realized among various domains, their impact  on agriculture field show potential research area.  In the context of machine learning,  the chances of achieving optimization level in each segment is more in the agriculture cycle. In this paper, we have discussed about the area of application in agriculture fields from the perspective of farmers. We have also reviewed in detail soil management process like soil moisture control, temperature prediction and checking nutrients of soil  in agricultural field with different machine learning algorithms. In addition, comparative study of algorithms for soil management is also presented.